Total Synthesis of 4α-Hydroxyallosecurinine and Securingine F, Securinega Alkaloids with a C4-Hydroxy Handle for Biofunctional Derivatizations - Park, Sangbin; Kim, Doyoung; Yang, Wooil; Han, Sunkyu (Synlett, 2023)
We describe the first total synthesis of the C4-hydroxylated securinega alkaloids 4α-hydroxyallosecurinine and securingine F. The synthetic route features an Ellman’s light-mediated hydrogen-atom-transfer-based epimerization reaction that effectively sets the desired configuration at the C2 position. Simultaneous skeletal rearrangement from neosecurinane to securinane frameworks and stereochemical reversal at the C4 site was achieved under Mitsunobu reaction conditions. The C4-hydroxy group is envisioned to serve as a handle for potential biofunctional derivatizations.
Keywords: total synthesis; securinega alkaloids; biofunctional derivatizations; hydroxyallosecurinine; securingine F